A intertextualidade entre Coraline e o mundo secreto e o mito de Orfeu - Barbosa, Nahinã de Almeida Rosa (2012)
This thesis aims to examine the update that the myth of Orpheus has suffered in the movie "Coraline" an adaptation of the British Neil Gaiman s novel "Coraline" (2003) , through a comparative and dialogic analysis, based on Bakhtin s concepts of dialogism, carnivalization and grotesque, between the original myth and its degradation in the film work. The proposal of a dialogic study between the myth of Orpheus and the movie happens not only because of the dessacralization that the myth has suffered, but also for the common theme of the katabasis, since Coraline and Orpheu made it to rescue something that was taken from them, whether it was the loved one or the recognition of the family and own values. After this analysis, based on Mircea Eliade s, Pierre Brunel s and João Batista de Brito s studies, the double was shown as an increase that the myth has suffered on this update and the reason why there was the manifestation of the double in this work was elucidated.